Revealing ecotype influences on Cistanche sinensis: from the perspective of endophytes to metabolites characteristics - Zhang, Min; Miao, Yujing; Zhang, Xinke; Sun, Xiao; Li, Minhui; Huang, Linfang (Frontiers in Microbiology, 2023)
Plant microorganism is critical to plant health, adaptability, and productive forces. Intriguingly, the metabolites and microorganisms can act upon each other in a plant. The union of metabolomics and microbiome may uncover the crucial connections of the plant to its microbiome. It has important benefits for the agricultural industry and human being health, particularly for Chinese medical science investigation. In this last two years study, on the strength of the UPLC-MS/MS detection platform, we accurately qualitatively, and quantitatively measured the Cistanche sinensis fleshy stems of two ecotypes. PhGs metabolites including echinacoside, isoacteoside, and cistanoside A were significantly downregulated at two ecotypes of Cistanche sinensis. Add up to 876 metabolites were monitored and 231 differential metabolites were analyzed. Further analysis of 34 core differential metabolites showed that 15 compounds with up-regulated belonged to phenolic acids, flavonoids, and organic acids, while 19 compounds with down-regulated belonged to phenolic acids, flavonoids, alkaloids, amino acids, lipids, and nucleotides. Thereafter, through high-throughput amplicon sequencing 16S/ITS sequences were procured. There was no noteworthy discrepancy in the endophytic bacteria’s α and β diversity between sandy and loam ecotypes. By comparison, the α and β diversity of endophytic fungi was notably distinct. The fungal community of the loam ecotype is more abundant than the sandy ecotype. However, there were few such differences in bacteria. Most abundant genera included typical endophytes such as Phyllobacterium, Mycobacterium, Cistanche, Geosmithia, and Fusarium. LEfSe results revealed there were 11 and 20 biomarkers of endophytic bacteria and fungi in C. sinensis at two ecotypes, respectively. The combination parsing of microflora and metabolites indicated noteworthy relativity between the endophytic fungal communities and metabolite output. Key correlation results that Anseongella was positive relation with Syringin, Arsenicitalea is negative relation with 7-methylxanthine and Pseudogymnoascus is completely positively correlated with nepetin-7-O-alloside. The aim of this research is: (1) to explore firstly the influence of ecotype on Cistanche sinensis from the perspective of endophytes and metabolites; (2) to investigate the relationship between endophytes and metabolites. This discovery advances our understanding of the interaction between endophytes and plants and provides a theoretical basis for cultivation of C. sinensis in future.